Unlocking employee performance: the chain effect of servant leadership, organizational culture, and organizational commitment - Marumpe, Dody Pratama; Jaya, Arman; Nabila, Amaninda Jihan; Adelia, Steven (Jurnal Mantik, 2025)
A This study aims to examine the influence of servant leadership and organizational culture on employee performance, with organizational commitment serving as a mediating variable at PT Taspen (Persero) Pontianak Branch. The research employs a quantitative descriptive approach using both primary and secondary data. The population consists of all employees at PT Taspen (Persero) Pontianak Branch, with a census or saturated sampling technique involving 102 respondents. Data analysis was conducted using SmartPLS4 version 4.1.0.2. The results indicate that both servant leadership and organizational culture have a direct and significant effect on organizational commitment, as well as a direct and significant effect on employee performance. Furthermore, organizational commitment also has a direct and significant impact on employee performance. The findings also demonstrate that organizational commitment mediates the relationship between servant leadership and organizational culture on employee performance. Theoretically, this study provides an important contribution to the understanding of factors that influence employee performance, particularly within the context of PT Taspen (Persero) Pontianak Branch